INFLUENCE OF ORGANIZATIONAL STRUCTURE OF EFFECTIVENESS OF BIRTH CERTIFICATE OF SERVICE IN THE DEPARTMENT OF POPULATION AND NOTES CIVIL DISTRICT OF SOUTH MINAHASA - Waworuntu, Chindy Thalia; POSUMAH, JOHNNY HANNY; Sampe, Stefanus (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT :The organizational structure is very interesting to observe because of its activities in order to meet the needs of citizens for services and service. Orientation in their activities so that the organizational structure in diamika life, society acting as a consumer engaged in service activities. The effectiveness of the service that has been happening in Indonesia, both the center and the area can not be denied there are still many problems that occur, although not all regions have the effectiveness of public services are bad, are like the uncertainty of the time, cost and method of service, discrimination in services, extortion and other highly far from the ideal of public service organizations. This study titled organizational structure influence the effectiveness of service to the birth certificate at the Department of Population and Civil Registration South Minahasa district to give satisfaction to the public. Methods This study used quantitative approach this type of research. The focus of this research is how the organizational structure of the effectiveness of service to the birth certificate at the Department of Population and Civil Registration South Minahasa district to give satisfaction to the people and the area around the center. Based on the research that has been done, then the writer can draw the conclusion that the quality of public services in the Department of Population and Civil Registration South Minahasa district, especially in the birth certificate of quality can be said.Keyword: "Organizational Structure, Effectiveness of Service"